Synthesis of Phosphatic Sediment-Faunal Relationships Within the Pungo River Formation: Paleoenvironmental Implications - Snyder, Scott W.; Riggs, Stanley R.; Katrosh, Mark R.; Lewis, Don W.; Scarborough, A. Kelly (My University, 1982)
The lower part of the Pungo River Formation in the Aurora Embayment (units A and B) consists of phosphorite sands and interbedded dolomites that grade southward into calcareous quartz sand (unit CC) associated with a pre-Miocene topographic high. Within this embayment phosphate content decreases southward and becomes negligible in unit CC. Units A and B contain foraminiferal assemblages whose most abundant specimens range from rare to absent in these units. Similar assemblages persist as the units thicken to the east. The sporadic occurrence of more diverse species associations in units A and B suggests that the depositional embayment was not restricted; but conditions were not generally suitable for most open shelf species. The predominance of Buliminella elegantissima, which flourishes in sewage outfall areas in modern seas, suggests that water chemistry or organic nutrient supply, perhaps related to phosphate genesis, limited foraminiferal faunal diversity. Upper Pungo River sediments within the Aurora Embayment (units C, D, and DD) consist of phosphorite sands and interbedded phosphatic, quartz-bearing, moldic limestones. Units C and DD also grade southward into the calcareous quartz and of unit CC. These upper units contain richer, more diverse benthic assemblages with high frequencies of middle and outer shelf species. Planktonic specimens are common within these units. Unlike the assemblages of units A and B, those of unit C suggest no unusual depositional conditions. Phosphorites of unit C are richer in phosphatic sediments than are those of units A and B. The enrichment may reflect concentration by physical sedimentary processes. Faunal and sedimentary characteristics suggest that the phosphate of unit C was transported, perhaps being derived from adjacent areas of the embayment or directly from underlying units (A and B), in which the phosphorites appear to have formed in situ.
Keywords: Pungo River Formation (N.C.); Aurora Embayment (N.C.); Dolomites; Phosphate; Buliminella elegantissima; Benthic; Faunal